2012
DOI: 10.1039/c2an35612k
|View full text |Cite
|
Sign up to set email alerts
|

Glucose sensor based on an electrochemical reduced graphene oxide-poly(l-lysine) composite film modified GC electrode

Abstract: A convenient and environmentally friendly method of fabricating glucose biosensors is proposed. Glucose oxidase (GOD) was immobilized on electrochemically reduced graphene oxide (ERGO) which was adsorbed on the poly-L-lysine (PLL) modified glassy carbon electrode after being immersed in GO solution for 4 h. The electrochemical behaviors of GOD/ERGO/PLL/GC electrode have been investigated by cyclic voltammetry. Direct electron transfer between GOD immobilized with ERGO/PLL and GC electrode was observed. Moreove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 26 publications
0
21
0
1
Order By: Relevance
“…The combination of both materials can offer a biocompatible environment for the following functionalization or the adsorption of biomolecules. Therefore, some biosensors have been fabricated based on PLL-graphene composites for glucose [27], H 2 O 2 [28,29], cancer cells [30] and genes [31]. Although studies on the detection of DA or AA based on PLL-modified electrodes have been previously published [32,33], no work has been reported on the application of PLL/GO-modified electrodes for simultaneous electrochemical studies of DA and UA.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of both materials can offer a biocompatible environment for the following functionalization or the adsorption of biomolecules. Therefore, some biosensors have been fabricated based on PLL-graphene composites for glucose [27], H 2 O 2 [28,29], cancer cells [30] and genes [31]. Although studies on the detection of DA or AA based on PLL-modified electrodes have been previously published [32,33], no work has been reported on the application of PLL/GO-modified electrodes for simultaneous electrochemical studies of DA and UA.…”
Section: Introductionmentioning
confidence: 99%
“…In order to understand better electron-transfer mechanism of enzymes or proteins and eventually to develop sensitive enzyme or protein-based biosensors, we attempt to utilize graphene nanoplatelets (GNPs), multi-layered graphene, as the electrode material for the realization of the electron transfer of HRP. This idea is different from those published in the literature, where either a single-layered graphene, the reduced graphene, the graphene nanocomposite, or the functionalized graphene [12,[28][29][30][31][32] was utilized as the electrode to immobilize HRP. The advantages of GNPs we used over graphene adopted in previous publications are easy synthesis and facile handling but possessing similar electrochemical properties.…”
mentioning
confidence: 99%
“…Therefore, the analytical performance of the Au/CA/(GOx/ TFGn) n can be regulated by adjusting the number of GOx/TFGn bilayers. This is significantly different from other graphene-based glucose biosensors, in which glucose oxidase was immobilized in a monolayer of graphene and thus the amperometric response could not be modulated [7,10,46].…”
Section: Analytical Performance Of the Biosensormentioning
confidence: 90%
“…Graphene exhibits excellent electrical conductivity, strong mechanical strength, high thermal conductivity and a high surface area [1][2][3][4][5][6]. The planar morphology and larger surface area together with its excellent electrical conductivity make graphene an ideal material for electrochemical sensors [7][8][9], and graphene may perform better than any other carbon-based electrodes as a sensor material [10]. Recently it was shown that the graphene-based electrodes can provide excellent capability in ultra sensitive electrochemical detection of single nucleotide polymorphisms of DNA [11] and early detection of leukemia using DPV [12][13].…”
Section: Introductionmentioning
confidence: 99%